Maize leaf rolling and its response to drying soil and evaporative demand - Echarte, Laura; Sinclair, Thomas; Jafarikouhini, Nahid (Wiley, 2024)
Leaf rolling is an adaptive mechanism associated with water deficiencies; however, the physiological processes and environmental factors contributing to leaf rolling are not fully understood. The objective of this study was to examine (i) a possible relationship between the degree of leaf rolling and soil water content and (ii) the possible influence of vapor pressure deficit (VPD) on the degree of leaf rolling. Leaf rolling was measured on maize (Zea mays L.) plants grown in pots and subjected to various soil drying and atmospheric VPD treatments. The experimental results indicated that (i) high VPD by itself does not readily induce leaf rolling, and (ii) leaf rolling was observed in proportion to the extent of soil drying. The values of the fraction of transpirable soil water thresholds for the decline in normalized transpiration rate and for the initiation of plant leaf rolling were sensitive to environmental conditions (VPD and temperature). With soil drying, leaf rolling was initiated slightly after the initiation of a decrease in the transpiration rate.